The Review of Theoretical Bankruptcy Banking After the Global Financial Crisis - Ummah, Shinta Hidayatul; Suhartono, Suhartono; Mongid, Abdul (Institut Teknologi Sepuluh Nopember, 2020)
Every company is vulnerable to bankruptcy, including banking industry. Bankruptcy of a bank will have an effect on other industries, because it as intermediation institution. If the intermediation process is stalled, the payment system will stall and disturb economic activities. Therefore research about indicator to predict the bankruptcy is important. Risk management must be implemented to detect and manage risk arising from bank operations. Banks can manage bankruptcy risk from the efficiency side. This study focus on the effect financial ratio (Return on Assets and Equity to Total Assets), size bank, and macroeconomic to bankruptcy predictions. Most of the bank's revenue from credit, it is on the asset side in the balanced sheet. If the bank has small assets then potentially have financial distress. The paper aims to conceptually and based on theoretical review studies. There are signaling and efficiency theory as basic theories related with these concept. By classifying the result of previous research, found some propositions: Return on Asset, Equity to Total Asset, Size Bank, Inflation and Gross Domestic Product are able to predict bank bankruptcy. The research believes that the proposition of this study result can be tested empirically mainly in banking industry